Currently available first-line drug therapies for treating pancreatic cancer. (22nd November 2018) - Olson, Jennifer L.; Bold, Richard J.
ABSTRACT: Introduction: Pancreatic adenocarcinoma is the 9th most common cancer in the United States and the 4th most common cause of cancer-related death given its poor prognosis. Areas covered : The authors have performed a literature search for pertinent published clinical trials, ongoing Phase 3 clinical trials, and current treatment guidelines using PubMed, Clinicaltrials.gov, and NCCN, ASCO, ESMO, and JPS websites. The review itself discusses landmark studies and ongoing research into the chemotherapy regimens recommended by each oncologic society. The authors also examine drugs that were promising but failed in Phase 3 trials and those currently being investigated. Finally, the authors provide their expert opinion on the subject and provide their future perspectives. Expert opinion: While advances in chemotherapy for pancreatic cancer have been limited in comparison to other cancers, there have been improvements in survival. Combination therapy and a goal of R0 resection are key elements to extend life. Novel agents directed at the unique properties of pancreatic cancer are promising.